THE CORRELATION OF MUHADHOROH TRAINING AND STUDENTS’ PUBLIC SPEAKING AT AN ISLAMIC BOARDING SCHOOL TANGERANG - Fathimah Fathratul Umyun; Dyah Supraba Lastari; Yudhie Indra Gunawan (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
This study aimed to determine whether there is a correlation between students’ public speaking and muhadhoroh training with the title “The Correlation of Muhadhoroh Training and the Eighth Grade Students’ Public Speaking at Al-Manshuriyah Islamic Boarding School Tangerang”. The research subjects in this study were 28 eighth grade students. The research was quantitative survey method. The data instruments were tests and questionnaires. The test was used to collect data on students’ public speaking using speech test. Researchers used SPSS 25 and Ms. Excel to analyzed data. The result showed that there was significant relationship between muhadhoroh training and students’ public speaking. This could be seen from the results of a significant correlation in public speaking and muhadhoroh training  _xy = 0,897>  _t = 0,374, N = 28 with a significant value 0,05 so there is a correlation. Keywords: correlation study, public speaking, muhadhoroh training.